G242(P) Regular Education and Audit Improves the Management of Pain in Children. (4th June 2013) - Waterfield, T; Anpananthar, A; Gandhi, G; Thomson, J
Abstract : Aims: All children have the right to appropriate prevention, assessment and control of pain yet the assessment and management of pain in children is often inadequate 1, 2 . We therefore set out to assess and address problems within our own Paediatric Emergency department (ED) relating to pain management in children because it has been shown that unrecognised and poorly managed pain can become established, severe and difficult to control 3, 4, 5 . Methods: We retrospectively audited 100 ED patient records to assess: The proportion of patients that had their pain assessed at triage The use of analgesia against the department's pain protocol We also conducted a parallel audit to assess the confidence of all ED staff in assessing pain in verbal and pre-verbal children. The above audits were then repeated following an intervention involving the dissemination of audit data as well as the delivery of teaching sessions that had been designed around our hospital's pain protocol. The sessions were provided for all ED staff and focussed on using the Face, Legs, Arms, Cry, Consolability (FLACC) score and the Wong and Baker (smiley faces) score used in our hospital 6, 7 . In addition laminated score cards were placed in the ED to be used as an aide memoire. Results: 16% of patients in the initial audit had their pain recorded at triage with this rising to 72% following our interventions. In those patients with documented pain scores the use of analgesia was as per the guideline in 100% of cases. We also found that prior to our interventions ED staff were only confident 28% and 84% of the time when assessing pain in pre-verbal and verbal children respectively. Following our educational sessions confidence with regards to pain scoring had risen to 96% and 100% for pre-verbal and verbal children respectively. Conclusion: Our experience suggests that the assessment process is the most important step towards good pain management in children within the ED setting. A programme of regular audit and education is vital for raising awarenss and confidence amongst healthcare professionals.